2016
DOI: 10.1177/0218492316654774
|View full text |Cite
|
Sign up to set email alerts
|

Mini-aortic surgery with percutaneous cannulation and rapid-deployment valve

Abstract: The combined use of rapid-deployment valves, percutaneous cardioplegia, and left heart venting is safe and effective and allows a significant reduction of the skin incision together with a significant reduction of intraoperative times without affecting hospital outcomes or hemodynamic performance of the prosthetic valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The risk of the need for PPM insertion after AVR was drawn from 17 studies with 2435 patients [5][6][7][13][14][15][16][17][18][19][21][22][23][26][27][28][29] after the exclusion of 1 study that reported no patients with a PPM insertion. 20 The pooled analysis showed that the risk of PPM insertion was significantly higher in the RDAVR group than in the CAVR group (RR, 2.08; 95% CI, 1.49-2.90; I 2 ¼ 0%). The risk of PPM was also significant in pooled estimates from the adjusted results from 9 studies (Figure 4).…”
Section: Risk Of Postoperative Complications: Ppm Insertionmentioning
confidence: 92%
See 4 more Smart Citations
“…The risk of the need for PPM insertion after AVR was drawn from 17 studies with 2435 patients [5][6][7][13][14][15][16][17][18][19][21][22][23][26][27][28][29] after the exclusion of 1 study that reported no patients with a PPM insertion. 20 The pooled analysis showed that the risk of PPM insertion was significantly higher in the RDAVR group than in the CAVR group (RR, 2.08; 95% CI, 1.49-2.90; I 2 ¼ 0%). The risk of PPM was also significant in pooled estimates from the adjusted results from 9 studies (Figure 4).…”
Section: Risk Of Postoperative Complications: Ppm Insertionmentioning
confidence: 92%
“…Therefore, a total of 21 studies were included in this review ( Figure E1). [4][5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations